GAMBARAN KECEMASAN PADA WANITA PEKERJA TEMPAT HIBURAN MALAM (WANITA PENGHIBUR) - ., Hairul . (MOTIVASI, 2016)
ABSTRACT            Anxiety is an uncomfortable feeling, in the form of uncertainty about something that has not happened, followed by the presense of body sensations. Working as women workers at the night clubs whom often called as the woman entertainers is a work that has a lot of risks for the onset of anxiety. The purpose of this research is to get a sense of anxiety felt by women entertainers. This research is a qualitative descriptive study which using techniques of data collection through observation, interview, and documentation. As a result of this research found that the main factor of the Subject who work as an entertainer is as a form of escape, then the factor of economy and the convenience to get money is the motivation factors to stay afloat at their work. There are four factors discovered in the emergence of anxiety on women workers at the night clubs just as follows: anxiety of health declining with low level of anxiety, moral anxiety with low level of anxiety, the anxiety about the raid with high level of anxiety, and anxiety of violence and sexual abuse with medium level of anxiety going to panic.Intisari                   Kecemasanadalahperasaansangattidaknyaman,berupaketidakpastiantentangsesuatuyangbelum terjadi,diikutiolehadanyasensasitubuh. Wanita pekerja tempat hiburan malam yang biasa disebut dengan wanita penghiburmerupakanpekerjaanyangbanyak memilikirisikountuktimbulnyakecemasan.Tujuandari penelitian ini adalah untuk mendapatkan gambaran kecemasan yang dirasakan oleh wanita pekerja tempat hiburan malam (wanita penghibur).Penelitian ini termasuk penelitian deskriptifkualitatifdenganteknik pengambilan data melalui observasi, wawancara, dan dokumentasi. Dari hasil penelitian ini didapatkan bahwa penyebab Subjek bekerja sebagai wanita penghibur adalah sebagai bentuk pelarian, kemudian faktor ekonomi dan mudahnya mendapatkan uang menjadi pendorong untuk tetap bertahan pada pekerjaan itu. Didapatkan 4 faktor timbulnya kecemasan pada wanita pekerja tempat hiburan malam yaitu sebagai berikut: kecemasan terhadap menurunnya kesehatan dengan tingkat kecemasan ringan, kecemasan moral dengan tingkat kecemasan ringan, kecemasan terhadap razia dengan tingkat kecemasan berat, dan kecemasan terhadap kekerasan dan pelecehan seksual dengan tingkat kecemasan sedang hingga panik.